2016
DOI: 10.1021/acs.jpcc.6b04398
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of ALD Encapsulation of Quantum Dots: Embedding Supported CdSe/CdS/ZnS Quantum Dots in a ZnO Matrix

Abstract: We study the encapsulation of monolayers of CdSe/CdS/ZnS core/shell/shell quantum dots (QDs) in a ZnO matrix by atomic layer deposition (ALD) in order to gain insight in the interaction between quantum dots and ALD precursors and the resulting metal oxide coating. Using in situ XRF and GISAXS, we show the inhibition of ZnO growth on as-deposited QDs. Growth can, however, be triggered by exposing the QDs to a single pulse of trimethyl­aluminum (TMA) vapor. Such a TMA pretreatment results in the substitution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 33 publications
0
40
0
Order By: Relevance
“…atomic layer deposition. [53] As such, when encapsulating QDs into SiNx, the host permittivity is closer to that of air/ligands, than that of SiNx (see also Fig. 8d).…”
Section: A Refractive Index Of Qd Compositesmentioning
confidence: 83%
“…atomic layer deposition. [53] As such, when encapsulating QDs into SiNx, the host permittivity is closer to that of air/ligands, than that of SiNx (see also Fig. 8d).…”
Section: A Refractive Index Of Qd Compositesmentioning
confidence: 83%
“…In recent years, several groups have explored extending this concept of using light to study ALD growth towards the x-ray part of the electromagnetic spectrum. 8,[10][11][12][13][14][15][16][17][18][19][20][21][22][23] Indeed, when an ALD reactor is equipped with x-ray transparent windows (e.g., beryllium, graphite, or kapton), then the film can be (intermittently) exposed to x-rays during growth, and a wide range of x-ray based thin film characterization techniques can be used for in situ characterization, as recently reviewed by Devloo-Casier et al 17 Since ALD is typically used for nanocoatings with a thickness of 0.1 to several tens of nanometers, while xrays typically penetrate several micrometers deep into most materials, it is challenging to obtain a sufficient signal to noise ratio for x-ray based characterization techniques, in particular when targeting acquisition rates of 1-60 s in order not to interfere too much with the standard exposure cycle of the ALD process. Therefore, while lab-based x-ray sources are used routinely for ex situ analysis of, e.g., the crystallinity of ALD grown films, the in situ studies typically require the high photon flux that can only be offered by synchrotron based sources.…”
Section: Introductionmentioning
confidence: 99%
“…30 In ALD research, in situ GISAXS has been applied to investigate conformal deposition in porous thin films 18 and on a layer of semiconducting quantum dots. 23 In addition, GISAXS is greatly suitable for monitoring the morphological evolution during ALD of noble metals. 20,31,32 In these processes, including ALD of ruthenium, the growth is usually initiated in localized islands spread across the surface, which give rise to a scattering pattern in GISAXS that can be analyzed to extract information about the island dimensions and arrangement on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Silica has also been used as am atrix to protect inorganic perovskite QDs. [16][17][18][20][21][22][23][24][25] However,n oa pplication to perovskite QDs has been reported thus far.T he high sensitivity to moisture,t emperature,a nd light of this class of QDs makes the development of an optimal ALD process not trivial. Thebottom line is that while for organic-inorganic perovskites,d ifferent stabilizing approaches have been successfully implemented, which are based mostly on polymers,noreliable approach exists for inorganic perovskite QDs.…”
mentioning
confidence: 99%
“…[16][17][18][19] Previous works have shown that metal oxide matrices (Al 2 O 3 and ZnO) improve the oxidative and photothermal stability of other QDs (PbSe,P bS,C dSe, CdSe@ZnS,a nd CdTe). [16][17][18][20][21][22][23][24][25] However,n oa pplication to perovskite QDs has been reported thus far.T he high sensitivity to moisture,t emperature,a nd light of this class of QDs makes the development of an optimal ALD process not trivial. Fore xample,l ow temperature and short water pulses are mandatory to avoid QD degradation.…”
mentioning
confidence: 99%